2003
DOI: 10.1063/1.1532728
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian dynamics from a simulation of a short peptide: Loop closure rates and effective diffusion coefficients

Abstract: Intrachain contact formation rates, fundamental to the dynamics of biopolymer self-organization such as protein folding, can be monitored in the laboratory through fluorescence quenching measurements. The common approximations for the intrachain contact rate given by the theory of Szabo, Schulten, and Schulten (SSS) [J. Chem. Phys. 72, 4350 (1980)] and Wilemski-Fixman (WF) [J. Chem. Phys. 60,878 (1973)] are shown to be complementary variational bounds: the SSS and WF approximations are lower and upper bounds, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 49 publications
2
48
0
1
Order By: Relevance
“…37 Various simulations suggest that these theories represent complementary bounds of end-to-end contact formation rates in a Gaussian chain. 38,39 However, for real polymer chains the proposed scaling laws deviate for short chains due to chain stiffness influencing intrachain diffusion over short peptide segments. Flory introduced the characteristic ratio C N as a measure for the dimensions of a stiff chain compared to a freely jointed chain (FJC): 40…”
Section: Effect Of the Chain Length On End-to-end Contact Formationmentioning
confidence: 98%
“…37 Various simulations suggest that these theories represent complementary bounds of end-to-end contact formation rates in a Gaussian chain. 38,39 However, for real polymer chains the proposed scaling laws deviate for short chains due to chain stiffness influencing intrachain diffusion over short peptide segments. Flory introduced the characteristic ratio C N as a measure for the dimensions of a stiff chain compared to a freely jointed chain (FJC): 40…”
Section: Effect Of the Chain Length On End-to-end Contact Formationmentioning
confidence: 98%
“…Note that the boundaries between Regions I and II are not sharp but are crossovers. Loop-formation kinetics in the crossover area will likely combine aspects of both regimes, as indicated in recent simulations [10] and by results that show that τ SSS and τ Doi are respectively lower and upper bounds for τ c [11]. Similarly, based on their BD simulation results, Podtelezhnikov et al [27] suggested that τ c ≃ τ R /α near the boundaries.…”
mentioning
confidence: 93%
“…The discrepancy between the two continues to spur debate [10,11]. For the important case of stiff chains [12,13], where the polymer length L is not too much longer than the persistence length ℓ p , only limited numerical results are known [see, for example, [14,15] and references therein].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The two most commonly used approximations, the Szabo–Schulten–Schulten (SSS) theory27 and the Wilemski–Fixman (WF) approximation,15 utilize two different local equilibrium approximations for the polymer dynamics and cannot be systematically improved in any straightforward way. Computer simulations2,3,69,12 have provided further insights and revealed the limitations inherent in these approximations. A recent paper by Thirumalai and co-workers12 presents a comprehensive comparison of various theories with the results of such simulations.…”
Section: Introductionmentioning
confidence: 99%